Systematic review and meta-analysis on the relationship between prenatal stress and metabolic syndrome intermediate phenotypes - Burgueño, Adriana Laura (2020)
Fil: Burgueño, Adriana. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina